ANALISIS PENGEMBANGAN PARIWISATA BERBASIS BUDAYA (CULTURAL TOURISM) DI KAWASAN CONDET KELURAHAN BALEKAMBANG, KECAMATAN KRAMAT JATI, JAKARTA TIMUR - Insani, Ichsan Aji (Penerbit Lafadz Jaya, 2023)
This study aims to determine the cultural potential that can be used as cultural tourism in Balekambang Village, Kramat Jati District, East Jakarta. The research method used in this study is descriptive qualitative and uses an observation approach based on the 3A analysis theory and SWOT analysis theory. Based on the 3A analysis theory and SWOT analysis theory with data triangulation analysis techniques from interviews with key informants and supporters, the prominent cultural potential in Balekambang Village is traditional food culture, martial arts and cultural performances, history of a place, and religion. As for the results of the observation findings, there is a very strong religious culture, this is indicated by the many graves of religious figures or habibs in Balekambang Village and there are many assemblies, Islamic schools, and Islamic boarding schools. Then for the community itself, it has encouraged the traditional culture typical of Balekambang Village, such as making traditional food and then selling it, making batik products to forming tourism awareness groups or POKDARWIS. Meanwhile, for the local government, they have started to support their areas to become cultural tourism areas by forming cultural village programs and decorating their areas with Betawi decorations. With the results of the analysis and findings, Balekambang Village has the potential to be used as cultural-based tourism.